2013
DOI: 10.1161/hypertensionaha.111.00226
|View full text |Cite
|
Sign up to set email alerts
|

Pravastatin Attenuates Hypertension, Oxidative Stress, and Angiogenic Imbalance in Rat Model of Placental Ischemia-Induced Hypertension

Abstract: Preeclampsia is a pregnancy-specific condition characterized by an imbalance of circulating angiogenic factors and new-onset hypertension. Although current treatment options are limited, recent studies suggest pravastatin may improve angiogenic profile and reduce blood pressure in preeclampsia. We hypothesized pravastatin would restore angiogenic balance and reduce mean arterial pressure (MAP) in rats with reduced utero-placental perfusion pressure (RUPP)-induced hypertension. Pravastatin was administered i.p.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
73
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(80 citation statements)
references
References 39 publications
5
73
0
2
Order By: Relevance
“…In the RUPP model, decreased VEGF could also potentially result in decreased complement control proteins, allowing increased complement activation as demonstrated in kidney endothelium (Mason et al, 2004;Kerr and Richards, 2012). Although a recent study by Weissgerber et al (2014) questions the validity of the enzyme-linked immunosorbent assay for measurement of VEGF in rat plasma and serum, our previous studies have reported decreased angiogenic potential via endothelial tube formation assays in RUPP compared with normal pregnant controls (Gilbert et al, 2012b;Bauer et al, 2013). Clearly, a re-evaluation of the methodology for assessing angiogenic factors in the rat circulation is needed, with additional studies to understand the relationship between angiogenic imbalance and complement activation/control proteins following placental ischemia.…”
Section: Discussionmentioning
confidence: 84%
“…In the RUPP model, decreased VEGF could also potentially result in decreased complement control proteins, allowing increased complement activation as demonstrated in kidney endothelium (Mason et al, 2004;Kerr and Richards, 2012). Although a recent study by Weissgerber et al (2014) questions the validity of the enzyme-linked immunosorbent assay for measurement of VEGF in rat plasma and serum, our previous studies have reported decreased angiogenic potential via endothelial tube formation assays in RUPP compared with normal pregnant controls (Gilbert et al, 2012b;Bauer et al, 2013). Clearly, a re-evaluation of the methodology for assessing angiogenic factors in the rat circulation is needed, with additional studies to understand the relationship between angiogenic imbalance and complement activation/control proteins following placental ischemia.…”
Section: Discussionmentioning
confidence: 84%
“…For instance, trials with pravastatin are underway to ameliorate preeclampsia by inhibiting HMG CoA reductase, but because statins are contraindicated in pregnancy, as this class of drugs has a high risk of teratogenic potential 27 . Interestingly, the mechanistic rationale for pravastatin use is its potential to up-regulate VEGF and PlGF and correct the angiogenic imbalance of excess sFlt-1 in RUPP rats 28 . While this rationale is consistent with our therapeutic approach, administering rhPlGF is likely to be a more direct and safer strategy to treat preeclampsia.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 However, the move to clinical trials is perhaps surprising given all the preclinical mechanistic evidence pointing to pravastatin as a therapeutic has been performed in animal models. [16][17][18][19] Work examining whether pravastatin has any biological effects in relevant human tissues is extremely limited. One recent study suggested that low-dose pravastatin has no effect on sFlt-1 or sENG secretion from placental explants obtained from 3 term preeclamptic women.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19] Surprisingly, in contrast to simvastatin, there has been little investigation into the effect of pravastatin on primary human tissues. It would be important to confirm whether pravastatin can in fact reduce sFlt-1 in primary human tissues or in placentas obtained from women with preeclampsia.…”
mentioning
confidence: 99%